The protein translocation channel mediates glycopeptide export across the endoplasmic reticulum membrane - Gillece, Pauline (The National Academy of Sciences, 2000)
Peptides and misfolded secretory proteins are transported efficiently from the endoplasmic reticulum (ER) lumen to the cytosol, where the proteins are degraded by proteasomes. Protein export depends on Sec61p, the ribosome-binding core component of the protein translocation channel in the ER membrane. We found that prebinding of ribosomes abolished export of a glycopeptide from yeast microsomes. Deletion of SSH1, which encodes a ribosome-binding Sec61p homologue in the ER, had no effect on glycopeptide export. A collection of cold-sensitive sec61 mutants displayed a variety of phenotypes: two mutants strongly defective in misfolded protein export from the ER, sec61-32 and sec61-41, displayed only minor peptide export defects. Glycopeptide export was severely impaired, however, in several sec61 mutants that were only marginally defective in misfolded protein export. In addition, a mutation in SEC63 strongly reduced peptide export from the ER. ER-luminal ATP was required for both misfolded protein and glycopeptide export. We conclude that the protein translocation channel in the ER membrane mediates glycopeptide transport across the ER membrane.